2017
DOI: 10.5005/jp-journals-10047-0029
|View full text |Cite
|
Sign up to set email alerts
|

Cracks and Fractures in Teeth

Abstract: Cracks and fractures in teeth are difficult to diagnose and treat, especially in the initial stages. The etiology of cracks is still obscure. With an increase in both geriatric population and tooth retention, the incidence of cracked teeth can also increase. There are many types of cracks from simple craze lines to vertical root fracture. An astute clinician should make crack detection a part of diagnostic screening. Proper diagnosis and treatment of cracked teeth is not possible without knowledge of the types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results are in accordance with previous published studies. Shemesh et al .,[ 11 ] Kumar and Subbiya,[ 12 ] and Harandi et al . [ 13 ] have also reported that canal preparation could cause significant dentinal defects.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in accordance with previous published studies. Shemesh et al .,[ 11 ] Kumar and Subbiya,[ 12 ] and Harandi et al . [ 13 ] have also reported that canal preparation could cause significant dentinal defects.…”
Section: Discussionmentioning
confidence: 99%